Chemically enhanced high-loaded membrane bioreactor (CE-HLMBR) for A-stage municipal wastewater treatment: Pilot-scale experiments and practical feasibility evaluation - He, Conghui; Wang, Kaijun; Wang, Wenchao; Luo, Juan; Fang, Kuo (Separation and purification technology, 2023)
[Display omitted] •A pilot scale chemically enhanced high-loaded membrane bioreactor was operated for over 8 months.•Stable filtration (flux 8–10 LMH) was achieved at SS over 15 g/L.•Over 75% soluble organics and phosphorous were removed by CE-HLMBR.•27–80 times concentration and over 85% concentration efficiency of COD were achieved. A-stage technology is acknowledged as a promising process for organic recovery. Due to its superior separation performance, the high-loaded membrane bioreactor (HLMBR) is a competitive variant of the A-stage. In this study, a pilot-scale chemically enhanced HLMBR (CE-HLMBR) was established to enhance the practical feasibility of the process. Polyaluminium chloride (PAC) and activated carbon (AC) were added to address membrane fouling, dependence on intensive aeration, and inadequate concentration factors. Eight conditions were designed to investigate the role of chemicals and aeration in filtration, pollutant removal, and organic recovery. Stable filtration (8–10 LMH) was achieved at SS concentrations of 15–20 g/L, benefiting from the dynamic formation and shedding of the protective cake layer, as well as the reduction of extracellular polymer substances (EPS). Over 75 % soluble organics and 80 % soluble phosphorous were removed by CE-HLMBR, mainly subject to the chemicals. Simultaneous nitrification–denitrification occurred due to uneven oxygen distribution. The influent organics were concentrated by factors ranging from 27 to 80 and the loss rate was less than 15 %. Meanwhile, methane production may not be an efficient method of resource extraction. The practical feasibility of the proposed CE-HLMBR was confirmed based on an additional three-month stable operation. This study will open new possibilities for the application of HLMBR systems.